MORPHOLOGICAL CHANGES IN PERIODONTAL TISSUES OF RATS IN THE EXPERIMENTAL MODEL OF TYPE 2 DIABETES MELLITUS - Artemchuk, A.V.; Savychuk, O.V.; Ostapko, O.I.; Krychkevych, V.A.; Koval, O.I. (World of Medicine and Biology, 2021)
Diabetes mellitus is one of the most common endocrine diseases, which prevalence is growing rapidly every year. The main pathogenetic factor of diabetes mellitus is persistent hyperglycemia and changes in the vascular walls of the microcirculatory bed. This leads to morphofunctional changes in the vascular wall, impaired permeability and trophism with progressive deterioration of hemodynamics and profound dystrophic changes, and, consequently, the inflammatory process's development. In the microcirculatory bed of the periodontium in patients with diabetes mellitus, there are pronounced changes in biochemical parameters of the blood and disturbed homeostasis, reduced resistance of periodontal tissues. This leads to increased exposure to periodontal pathogenic microflora, disrupts the integrity of the tooth-epithelial attachment, resorption of the cortical plate and the interdental septum, leading to tooth loss. The study of morphological changes in periodontal tissues of white Wistar rats in the conditions of experimental modelling of Type 2 diabetes mellitus is of great informational importance. This contributes to the development of measures aimed at preventing, early diagnosis, and effective treatment of periodontal diseases in patients with type 2 diabetes, especially in children and adolescents. Histological examination of morphological changes in periodontal tissues obtained with a microscope may be of practical use in future studies, serve to develop diagnostic, therapeutic and preventive measures for periodontal disease in children and adolescents with type 2 diabetes mellitus.
Keywords: diabetes mellitus; streptozotocin; pathogenetic mechanisms; periodontium; periodontal changes